Management is a Science - Gulick, Luther (Academy of Management Journal, 1965)
The article presents information on the implementation of management science to everyday management practice and describes the evolution of scientific thinking and the structural design of humans as it relates to memory and management. The author claims that management is a legitimate science because it seeks to understand why and how people work together systematically to accomplish common objectives and to make cooperative systems more useful to mankind. A discussion is presented about management's reliance on a number of other sciences in order to advance.